2011
DOI: 10.1371/journal.pone.0024235
|View full text |Cite
|
Sign up to set email alerts
|

In-Vivo Expression Profiling of Pseudomonas aeruginosa Infections Reveals Niche-Specific and Strain-Independent Transcriptional Programs

Abstract: Pseudomonas aeruginosa is a threatening, opportunistic pathogen causing disease in immunocompromised individuals. The hallmark of P. aeruginosa virulence is its multi-factorial and combinatorial nature. It renders such bacteria infectious for many organisms and it is often resistant to antibiotics. To gain insights into the physiology of P. aeruginosa during infection, we assessed the transcriptional programs of three different P. aeruginosa strains directly after isolation from burn wounds of humans. We compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
50
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(55 citation statements)
references
References 47 publications
(48 reference statements)
5
50
0
Order By: Relevance
“…The intercellular spaces in leaves are mostly filled with air [43] and very little is known about the mechanisms that plant pathogens utilize to obtain nutrients in this dry environment. Nitrogen limitation during P. aeruginosa infection in plants has been reported previously [44], [45]. One way that trehalose could promote nitrogen acquisition is by modulating host nitrogen metabolism, thereby diverting nitrogen-containing compounds to invading P. aeruginosa cells.…”
Section: Discussionmentioning
confidence: 87%
“…The intercellular spaces in leaves are mostly filled with air [43] and very little is known about the mechanisms that plant pathogens utilize to obtain nutrients in this dry environment. Nitrogen limitation during P. aeruginosa infection in plants has been reported previously [44], [45]. One way that trehalose could promote nitrogen acquisition is by modulating host nitrogen metabolism, thereby diverting nitrogen-containing compounds to invading P. aeruginosa cells.…”
Section: Discussionmentioning
confidence: 87%
“…We compiled lists from six transcriptomic (2,(83)(84)(85)(86)(87) and five proteomic (88-92) investigations of differential expression between biofilm and planktonic cells. This expands on previous analyses (93)(94)(95).…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have attempted to define the interaction dynamics between the pathogen and the host by studying gene and protein expression of either one or the other7891011. These studies have identified P. aeruginosa genes and virulence factors involved in bacterial attachment during colonization, nutrient acquisition, biofilm formation, or resistance to the immune system to facilitate persistence.…”
mentioning
confidence: 99%